Application of Precautionary Measures in the Use of Chemical Preparations in Agriculture (Eurasian Research Bulletin, 2023)
The article describes the necessary information about agriculture, plant protection, harmful insects, diseases, weeds, pesticides, organophosphorus compounds, humans and warm-blooded animals, rules of use, waiting period, biological efficiency, and environmental cleanliness.